Evaluation of Allylboronic Acid Pinacol Ester as Effective Shutdown Overcharge Additive for Lithium Ion Cells. Issue 2 (17th December 2016) - Streipert, Benjamin; Janßen, Pia; Cao, Xia; Kasnatscheew, Johannes; Wagner, Ralf; Cekic-Laskovic, Isidora; Winter, Martin; Placke, Tobias
Abstract : Allylboronic acid pinacol ester (ABPE) was investigated as shutdown overcharge additive to increase the intrinsic safety of lithium ion cells during operation at elevated charge cutoff potentials up to 4.5 V vs. Li/Li + . It was demonstrated that the additive had no negative influence on the cycling performance of LiNi1/3 Co1/3 Mn1/3 O2 (NMC-111)/graphite full cells operated in a standard operation voltage range between 2.5 V and 4.2 V. Electrochemical impedance spectroscopy was used to study the influence of the electrolyte additive on the impedance before and after overcharge and concomitant cell shutdown. Thereby, an immense increase in the charge transfer resistance after electrode shutdown was observed, thus, hinting to the formation of a lithium ion-insulating layer on the positive electrode surface. To further elucidate the working principle of the shutdown additive, surface investigations by means of scanning electron microscopy and X-ray photoelectron spectroscopy were carried out. The existence of a surface layer consisting mainly of polymeric species was proven. The presented results open up a new family of compounds for overcharge protection.